Development of an in vitro hairy root induction system in different soybean cultivars for gene expression and genome editing studies - Nhu Thao, Le Thi; Hong Nhung, Nguyen; Quang Huy, Le; Phuong Thao, Bui; Thu Ngoc, Le; Bich Ngoc, Pham; Hoang Ha, Chu; Tien Phat, Do (Vietnam Journal of Biotechnology, 2021)
Hairy root induction system has been widely applied for studies of gene function, gene expression, and genome editing in numerous plant species. In this study, we developed and evaluated the performance of an in vitro hairy root induction system via Agrobacterium rhizogenes on several Vietnamese and international soybean cultivars. The efficacy of in vitro hairy root induction and of transformation using this system was varied and depended on soybean cultivars as well as transgenic constructs. The hairy root induction frequency of different soybean cultivars ranged from 61.67% to 100% after 5 days on culture medium. From 43.8% to 79.8% of hairy roots transformed with GFP-expressing construct showed transgene expression, while that for the construct with the gus gene was from 38.07% to 72.33%. Among tested soybean cultivars, DT26 demonstrated the highest transformation and gene expression efficacy with both investigated vectors. This hairy root induction system was further utilized for targeted knockout mutagenesis via CRISPR/Cas9 of two genes which are G03 and G09 in the DT26 soybean cultivar. Successful mutagenesis in the regions of targeted genes was confirmed by shifted and multiple bands compared to which of non-transgenic hairy root in PAGE analysis. Sequencing results of targeted regions presented various nucleotide deletions ranging between -3 bp and -25 bp in size in both two genes of interest. This study laid an important basis for future gene function studies and targeted gene editing investigations on soybean plants in Vietnam.